Groundwater Hydrograph Decomposition With the HydroSight Model - Kong, Feihe; Song, Jinxi; Crosbie, Russell S.; Barron, Olga; Schafer, David; Pigois, Jon-Philippe (Frontiers in Environmental Science, 2021)
Groundwater, the most important water resource and the largest distributed store of fresh water in the world, supports sustainability of groundwater-dependent ecosystems and resilient and sustainable economy of the future. However, groundwater level decline in many parts of world has occurred as a result of a combination of climate change, land cover change and groundwater abstraction from aquifers. This study investigates the determination of the contributions of these factors to the groundwater level changes with the HydroSight model. The unconfined superficial aquifer in the Gnangara region in Western Australia was used as a case study. It was found that rainfall dominates long-term (1992-2014) groundwater level changes and the contribution rate of rainfall reduced because the rainfall decreased over time. The mean rainfall contribution rate is 77% for climate and land cover analysis and 90% for climate and pumping analysis. Secondly, the increasing groundwater pumping activities had a significant influence on groundwater level and its mean contribution rate on groundwater level decline is -23%. The land cover changes had limited influence on long-term groundwater level changes and the contribution rate is stable over time with a mean of 2%. Results also showed spatial heterogeneity: the groundwater level changes were mainly influenced by rainfall and groundwater pumping in the southern study region, and the groundwater level changes were influenced by the combination of rainfall, land cover and groundwater pumping in the northern study region. This research will assist in developing a quantitative understanding of the influences of different factors on groundwater level changes in any aquifer in the world.